Report on investigation into the sale of surplus public housing properties : ICAC report - New South Wales. Independent Commission Against Corruption; Cripps, Jerrold (Sydney : Independent Commission against Corruption, 2006)
"This report presents the results of an investigation ... into various circumstances between 1999 and 2005 relating to the sale of surplus properties from two public housing schemes known as HomeFund and Public Equity Partnership ("PEP"). The main subjects of the investigation were: Graham Wade, a former officer of the former Home Purchase Assistance Authority ... and NSW Department of Housing ... who was responsible for organising the sale of surplus HomeFund and PEP properties; John Ashe and Ken Williams, two real estate agents appointed by Mr Wade to sell such properties on behalf of the Authority and Department; and Leslie Green, Gabriel Lorentz and Frank Gelonesi, each of whom purchased one or more of those properties through companies they controlled. The Commission investigated whether any of these persons engaged in corrupt conduct."--p. 6.
"October 2006"
Commissioner: The Hon Jerrold Cripps QC.
Bibliographic references: p. 126-129
Also available online. Address as at 11/12/06: http://www.icac.nsw.gov.au/files/pdf/Report_on_investigation_into_the_sale_of_surplus_public_housing_properties__(Operation_Aztec_).pdf.
Keywords: Wade, Graham; Ashe, John; Williams, Ken; New South Wales. -- Department of Housing -- Corrupt practices; HomeFund; Public Equity Partnership (N.S.W.); Public housing -- New South Wales -- Management -- Corrupt practices